Is petitio principii a petitio principii? - Castro-Manzano, J. Martín (Aufklärung: journal of philosophy, 2018)
In this contribution we focus on the petitio principii fallacy and we review it under the tenets of different typical treatments. Then we submit the claim that petitio principii is indeed fallacious, not because of circularity—as the typical treatments suggest—, but because it fails to follow an order relation in Searle and Vanderveken's illocutionary logic. In other words, we claim that, although petitio principii arguments appear to be circular with respect to their propositional content, they are not circular with respect to their illocutionary acts. And hence, even when petitio principii arguments look like propositional loops and instances of reflexivity, they actually constitute a failure in an order relation, a non sequitur as it were.